Projektowanie "Portalu Informacyjnego UMK" - analiza makiet serwisu w oparciu o elementy user experience i architektury informacji - Cyrklaff-Gorczyca, Magdalena; Marzec, Paweł (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
The study aimed to compare three mockups (static graphic designs) of the Information Portal of the Nicolaus Copernicus University in Toruń in terms of user experience and information architecture indicators and identify the best one to use for creating an active website. The research used an eye-tracking method, usability tests, observations and surveys. Most respondents indicated that mockup no. 3 was the best of the three proposed static website page designs. The respondents justified their choice, among other things, by the fact that it was clear and easy to use, had a functional layout of information and an appropriate colour scheme. The design chosen by respondents has been improved to reflect their suggested modifications. Its final version can be viewed at https://portal.umk.pl/.